2021
DOI: 10.1021/acs.energyfuels.1c00792
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Measurement of Multiple Hydrate Structure Formation in Binary and Ternary Natural Gas Analogue Systems by Isochoric Equilibrium Methods

Abstract: Traditionally, it is commonly assumed that a single gas hydrate (or clathrate hydrate) structure/phase is formed in natural gas systemse.g., "s-II natural gas (NG) hydrates" or "s-I methane hydrates"based on that which is understood to be the most thermodynamically stable at incipient phase boundary conditions. This applies with respect to both studies of hydrates in natural sediments, and in the case of hydrocarbon production operations, including the testing of low-dosage hydrate inhibitors (LDHIs). Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…While NGs are normally assumed to just form a single structure-II hydrate, various hydrate phases of different structures and guest gas composition may actually form, including C 2–4 stabilized s-II, mixed C 1 /C 2 rich s-II/s-I, and (nearly) pure C 1 (s-I and potential s-II) at higher subcoolings. , Therefore, at higher Δ T sub , in addition to the most stable s-II natural gas hydrate, other hydrate structures are likely to form, which could play a role in KHI performance, e.g., due to the variable ability of polymers to inhibit these.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While NGs are normally assumed to just form a single structure-II hydrate, various hydrate phases of different structures and guest gas composition may actually form, including C 2–4 stabilized s-II, mixed C 1 /C 2 rich s-II/s-I, and (nearly) pure C 1 (s-I and potential s-II) at higher subcoolings. , Therefore, at higher Δ T sub , in addition to the most stable s-II natural gas hydrate, other hydrate structures are likely to form, which could play a role in KHI performance, e.g., due to the variable ability of polymers to inhibit these.…”
Section: Resultsmentioning
confidence: 99%
“…17,36,55−57 Although methane is generally known as an s-I former, s-II methane hydrate can be formed as a second phase (stable or potentially metastable) depending on pressure and temperature conditions. Although methane molecules can theoretically enter both cavities of s-II (5 12 and 5 12 6 4 ), its molecular diameter has historically been considered too small to stabilize the larger 5 12 6 4 cages. In contrast, methane molecules better stabilize the smaller 5 12 6 2 large cavities of s-I.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If there are no longer sufficient amounts of higher hydrocarbons for the formation of a structure II or structure H hydrate available in the feed gas phase, this may lead to the formation of a structure I CH 4 hydrate as a coexisting gas hydrate phase. This hypothesis of chemical fractionation of the feed gas phase was suggested as a possible explanation for the observation of the coexistence of hydrate phases in nature and laboratory experiments. ,, In contrast, the experimental work of Pan and Schicks showed that the depletion of the gas phase in structure-II-forming components does not necessarily result in the formation of a coexisting structure I hydrate phase . They were able to demonstrate in laboratory experiments that, even in a closed system with a limited amount of a complex feed gas mixture, a heterogeneous hydrate phase initially formed, which changed its composition over time.…”
Section: Introductionmentioning
confidence: 99%